Hydrometeorology Of Tropical Montane Rainforests Of Gunung Brinchang, Pahang Darul Makmur, Malaysia - Kolandai, Sanar Kumaran (2008)
In tropical montane forests, the negative impacts of climate change on biological diversity have been documented as a result of declining trend of cloud water interception. The objectives of this study were to describe the microclimate; quantify the hydrometeorological processes; determine the cloud water interception and describe elements of the canopy water balance model of two contrasting montane forest types in Cameron Highlands, Pahang, Malaysia. This study was conducted at two sites: lower montane forest (LMF: 1600 m a.s.l.; 4o30.25’N, 101’23’E) and an upper montane forest (UMF: 2031 m a.s.l.; 4o31’N, 101’23’E) of Gunung Brinchang. Using standard weather stations and louvered fog gauges, rainfall, P (mm), cloud water interception CWI (mm), air temperature T (oC), relative humidity RH (%), wind speed μ (m/s) and solar radiation Rs (MJ/m2/day) were recorded continuously at the two study sites from 1 November 2003 through 28 February 2005. In addition, throughfall Tf (mm) and stemflow, Sf (mm) in 0.02 ha forest plots were estimated weekly. Vegetation structure of trees (≥ 5 cm diameter) at both study plots were carried out. During the 16 month study period, a total of 2612 mm and 2736 mm of rainfall was recorded at the LMF and UMF sites, respectively. Storms (median duration 1.12 hr at LMF and 0.83 hr at UMF) were of low intensity (mean 1.72 mm/hr at LMF and 1.43 mm/hr at UMF). The results of diurnal and seasonal variation of rainfall show that more than 80% of the total rainfall occurred in the afternoon until late night (1200 to 2300 hrs). Amounts of cloud water intercepted by the canopy of LMF and UMF were estimated at 1.5% and 8.6% of P and were significantly different. The mean solar radiation for the LMF and UMF sites were, 11.9 MJ/m2/day and 10.3 MJ/m2/day, respectively. Consistently, lower air temperatures were recorded at the UMF site (14.3 to 16.2oC) compared to LMF (16.7 to 18.1oC), due to elevation differences. Total throughfall, Tf was 62.1% of rainfall in the taller LMF site and did not differ statistically from the stunted UMF site with 63.8%. The corresponding total stemflow (Sf ) amounts varied significantly for LMF and UMF sites, with 2.2% and 30.6% of rainfall, respectively. The rainfall interception, Ei at LMF was 37.4% of rainfall while at UMF; it was 5.7% of rainfall. Penman-Monteith evaporation ranged from 0.4 – 4.0 mm/day at LMF and 0.7 – 3.3 mm/day at UMF, respectively and was not significantly different. In conclusion, the study shows no difference in total rainfall and throughfall between LMF and UMF. However, significant differences were recorded in the 24-hour readings of cloud water, air temperature, relative humidity, solar radiation, wind speed and evaporation indicating altitudinal difference of the study sites. Quantitative evidence was obtained for the first time in Malaysia on selected elements of canopy water balance and a new eco-hydrological canopy water balance for Malaysian montane rainforests is proposed.